2023
DOI: 10.3390/biomedicines11030908
|View full text |Cite
|
Sign up to set email alerts
|

PDE3A and GSK3B as Atrial Fibrillation Susceptibility Genes in the Chinese Population via Bioinformatics and Genome-Wide Association Analysis

Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia, with uncovered genetic etiology and pathogenesis. We aimed to screen out AF susceptibility genes with potential pathogenesis significance in the Chinese population. Methods: Differentially expressed genes (DEGs) were screened by the Limma package in three GEO data sets of atrial tissue. AF-related genes were identified by combination of DEGs and public GWAS susceptibility genes. Potential drug target genes were selected using the DrugB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For example, Zhang et al have shown that CXCR4 and TYROBP are involved in the occurrence of AF, and the mechanism of action may be related to the activation of inflammatory pathways 19 . The PDE3A and GSK3B genes, as identified by Zhou et al, exhibit a significant association with the risk of AF in the Chinese population, providing a new theoretical basis for studying the pathogenesis of AF 20 . Based on WGCNA and machine learning techniques, Zhu et al found that NPPA , OMD , and PRELP could be used as diagnostic biomarkers for DCM combined with HF 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al have shown that CXCR4 and TYROBP are involved in the occurrence of AF, and the mechanism of action may be related to the activation of inflammatory pathways 19 . The PDE3A and GSK3B genes, as identified by Zhou et al, exhibit a significant association with the risk of AF in the Chinese population, providing a new theoretical basis for studying the pathogenesis of AF 20 . Based on WGCNA and machine learning techniques, Zhu et al found that NPPA , OMD , and PRELP could be used as diagnostic biomarkers for DCM combined with HF 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 19 The PDE3A and GSK3B genes, as identified by Zhou et al, exhibit a significant association with the risk of AF in the Chinese population, providing a new theoretical basis for studying the pathogenesis of AF. 20 Based on WGCNA and machine learning techniques, Zhu et al found that NPPA , OMD , and PRELP could be used as diagnostic biomarkers for DCM combined with HF. 21 These findings may help us better understand the pathogenesis of AF and HF, as well as facilitate the discovery of new diagnostic biomarkers or therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%